Morphometrical studies on black pepper (Piper nigrum L.). I. cluster analysis of black pepper cultivars - BABU, P N RAVINDRAN, R BALAKRISHNAN, K NIRMAL (Journal of Spices and Aromatic Crops, 1997)
Forty four cultivars and seven wild black pepper (Piper nigrum) accessions (51 Operational Taxonomic Units) were subjected to single linkage and centroid linkage cluster analysis. The 22 characters employed in the study resolved into two distinct sets. Based on character correlations, six clusters were recognised while certain characters did not show correlation with others. Centroid clustering led to the grouping ofthe Operational Taxonomic Units into 11 clusters. Among these, four groups had one cultivar, four had two cultivars, one had four cultivars, one had seven cultivars and one had 28 cultivars each. The cultivars that were unique and did not cluster with any other are Karimunda, Panniyur-1, Vadakkan and Kuthiravally. The inclusion of 28 cultivars in one group also shows that a majority of common cultivars resemble one another closely and probably had a common ongm. The study is useful in establishing the relative resemblances of major black pepper cultivars grown in Kerala and Karnataka of India.